Kanlungan a healing landscape for the patients and healthcare workers of Chinese General Hospital through redesigning Manila North Cemetery - Cabial, Robin Christian M.; Galingan, Zenaida C. thesis adviser (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The need to improve the physical and well-being of both patients and healthcare works is increasing as students show that they experience higher stress levels and burnouts than other sectors in the world. A solution to this increasing need is the immediate exposure of people to nature as recent researchers have brought up the healing benefits of nature to the well-being of a person or community. For the case of the residents of Chinese General Hospital, such a thing is needed as reports have surfaced in 2017 that showcase higher stress levels within the hospital's environment. Unfortunately, the institution has little to no space to provide their healthcare workers and patients the necessary green space needed for "healing" due to urbanization. Despite being surrounded by cemeteries, public cemeteries in the Metro are not without its problems. As is the case of Manila North Cemetery. Adjacent to the hospital, what was once one of the best and most attractive institutions of its kind in the Orient is now an overcrowded cemetery filled with apartment type tombs, informal settlers and bones. Through the integration of western and eastern healing landscape concepts in cemetery design, a healing landscape concepts in cemetery design, a healing landscape for the patients and healthcare workers of Chinese General Hospital can be achieved through redesigning Manila North Cemetery. Through the redesign, patients, healthcare workers and mourners alike can improve their physical and mental well-being, as well as their appreciation for life.
include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Cemeteries -- Landscape architecture